Bioethicists to the Barricades!. (24th July 2019) - Lindemann, Hilde
Abstract: In this article I begin with an anecdote as a way of exploring just exactly what activism entails. Are we talking about the kind of activism every citizen ought to engage in? Should we confine our topic to activism in health care settings? Just what is activism anyway, and how much and what kind ought bioethicists to engage in? Finally, I consider the possibility that it's perfectly permissible for bioethicists not to be activists of any kind.